Atypical Skeletal Muscle Profiles in Human Immunodeficiency Virus-Infected Asymptomatic Middle-Aged Adults. (25th December 2017) - Tran, Thanh; Guardigni, Viola; Pencina, Karol M; Amato, Anthony A; Floyd, Michael; Brawley, Brooke; Mozeleski, Brian; McKinnon, Jennifer; Woodbury, Erin; Heckel, Emily; Li, Zhuoying; Storer, Tom; et al.
Abstract : Concurrent characterization of skeletal muscle, physical function, and immune profile in middle-aged HIV-infected adults revealed atypical skeletal muscle with increased internalized myonuclei and decreased PGC-1α, in the context of fatigue, physical function deficits, and persistent inflammation and immune activation. Abstract: Background: Human immunodeficiency virus (HIV)–infected individuals are at increased risk of age-associated functional impairment, even with effective antiretroviral therapy (ART). A concurrent characterization of skeletal muscle, physical function, and immune phenotype in aviremic middle-aged HIV-infected adults represents a knowledge gap in prognostic biomarker discovery. Methods: We undertook a prospective observational study of 170 middle-aged, HIV-infected ambulatory men and women with CD4 + T-cell counts of at least 350/µL and undetectable plasma viremia while on effective ART, and uninfected control participants. We measured biomarkers for inflammation and immune activation, fatigue, the Veterans Aging Cohort Study mortality index, and physical function. A subset also received a skeletal muscle biopsy and computed tomography scan. Results: Compared to the uninfected participants, HIV-infected participants displayed increased immune activation ( P < .001), inflammation ( P = .001), and fatigue ( P = .010), and in a regression model adjusting for age and sex displayed deficits in stair-climb power ( P < .001), gait speed ( P = .036), and predicted metabolic equivalents ( P = .019). Skeletal muscle displayed reduced nuclear peroxisome proliferator-activated receptor-γ coactivator 1α–positive myonuclei ( P = .006), and increased internalized myonuclei ( P < .001) that correlated with immune activation ( P = .003) and leukocyte infiltration ( P < .001). Internalized myonuclei improved a model for HIV discrimination, increasing the C-statistic from 0.84 to 0.90. Conclusions: Asymptomatic HIV-infected middle-aged adults display atypical skeletal muscle profiles, subclinical deficits in physical function, and persistent inflammation and immune activation. Identifying biomarker profiles for muscle dysregulation and risk for future functional decline in the HIV-infected population will be key to developing and monitoring preventive interventions. Clinical Trials Registration: NCT03011957.